1998
DOI: 10.1074/jbc.273.32.20575
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phosphodiesterases 3B, 4A4, 4D1, 4D2, and 4D3 in Jurkat T-cells and in Human Peripheral Blood T-lymphocytes by 8-Bromo-cAMP and Gs-coupled Receptor Agonists

Abstract: In this study, a potential mechanism of ␤ 2 -adrenoreceptor desensitization has been explored that is based upon the enhanced degradation of cAMP by phosphodiesterase (PDE). Pretreatment of Jurkat T-cells with 8-bromo cAMP (8-Br-cAMP) or prostaglandin E 2 increased PDE3 and PDE4 activity in an actinomycin Dand cycloheximide-sensitive manner. This effect was associated with increased expression of HSPDE3B, HSPDE4A4, HSPDE4D1, HSPDE4D2, and HSPDE4D3 mRNA transcripts. Western analysis reproducibly labeled a band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 54 publications
7
72
1
Order By: Relevance
“…In fact, other molecules are likely involved in the transmission of the signal. One possibility is that the cAMP͞phosphokinase A pathway was responsible for PDE4 activation, as previously observed in activated T cells (31). However, we found that the phosphokinase A inhibitor (Rp-8-Br-cyclic AMPS) was unable to reduce IL-2 production in cells seeded on plates coated with anti-CD3͞CD28 mAbs Ϯ Tat, suggesting that in our cellular system PDE4 was not activated by the cAMP͞phosphokinase A pathway.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…In fact, other molecules are likely involved in the transmission of the signal. One possibility is that the cAMP͞phosphokinase A pathway was responsible for PDE4 activation, as previously observed in activated T cells (31). However, we found that the phosphokinase A inhibitor (Rp-8-Br-cyclic AMPS) was unable to reduce IL-2 production in cells seeded on plates coated with anti-CD3͞CD28 mAbs Ϯ Tat, suggesting that in our cellular system PDE4 was not activated by the cAMP͞phosphokinase A pathway.…”
Section: Discussioncontrasting
confidence: 38%
“…Five distinct functional domains have been characterized in the Tat protein: N-terminal (amino acids 1-21), cysteine-rich (amino acids [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], core (amino acids 38-48), basic (amino acids 49-57), and C-terminal (amino acids 58-86͞ 101; ref. 1).…”
mentioning
confidence: 99%
“…This mechanism has been well documented in several systems including S49 lymphoma cells, platelets, hepatocytes, adipocytes and Sertoli cells (for review, Giembycz, 1996;Perry et al, 2002). It has been demonstrated, in different human blood cells, that treatment with either b 2 -AR agonists (Manning et al, 1996;Seybold et al, 1998;Ortiz et al, 2000) or with a cAMP structural analogue, 8-Bromo-cAMP, leads to an upregulation of PDE4 enzymes. More recently, new evidences for a role of cAMP on PDE4 promoters have been defined (Vicini & Conti, 1997;D'Sa et al, 2002;Le Jeune et al, 2002).…”
Section: Rouget Et Almentioning
confidence: 92%
“…1999; Seybold et al. 1998). PDE4 inhibitors have proven potential as anti‐inflammatory drugs in chronic airway diseases.…”
Section: Introductionmentioning
confidence: 99%